EFFECT OF VARIOUS NUTRIENT SOURCES ON YIELD, YIELD ATTRIBUTES AND ECONOMICS OF GROUNDNUT (Arachis hypogaea L.) UNDER RAINFED AND PROTECTIVE IRRIGATED CONDITIONS - G. NARAYANA SWAMY*, A.V. NAGAVANI, K. C. NATARAJ, Y. REDDI RAMU; S. N. MALLESWARI (The Journal of Research ANGRAU, 2019)
The experiment was conducted during two consecutive Kharif seasons of 2014 and 2015 in groundnut.The highest level of yield attributes viz., number of filled pods plant-1, 100 pod weight, 100 kernel weight, shelling percentage, the lowest number of ill-filled pods plant-1, pod and haulm yield were recorded with the supply of 100 percent of N through sheep penning and found comparable with 50 per cent nitrogen through urea + 50 per cent nitrogen through FYM and recommended dose of fertilizer under rainfed situation. Whereas, under protective irrigation, which was inturn comparable with supply of 50 per cent nitrogen through urea + 50 per cent nitrogen through leaf compost. The highest gross returns and net returns in groundnut were obtained with supply of 100 per cent of N through sheep penning, which was at par with 50 per cent nitrogen through urea + 50 per cent nitrogen through FYM in both the situations during two consecutive years of investigation. The highest benefit-cost ratio was registered with supply of 100 per cent N through sheep penning, which was, however comparable with recommended dose of fertilizer under both situations except during second year under protective irrigation, where it was significantly superior over rest of the nutrient management practices tried.